Experiencia en la enseñanza-aprendizaje del área de ciencia y tecnología en la Institución Educativa N° 6010227 Club de Leones de Lemgo Alemania en la ciudad de Iquitos 2020-2022 - Rengifo Olórtegui, Jenny Ruth (2024)
His work presents the work experience in teaching Science and Technology after completing undergraduate studies in Biological Sciences at the secondary school level educational institution. The academic activities carried out within an academic year are showcased, using as an example the teaching of science and technology to three groups of fourth-grade students in the secondary level, labeled as "B," "C," and "D," at Educational Institution No. 6010227, Club de Leones de Lemgo Alemania, in the city of Iquitos, during the years 2020, 2021 y 2022. Additionally, the grades obtained during assessments of the developed competencies (C1: Inquires using scientific methods to construct knowledge, C2: Explains the physical world based on knowledge about living beings, matter and energy, biodiversity, earth and universe, and C3: Designs and builds technological solutions to solve problems in their environment) are discussed. The results showed promising progress in various competencies. In the "4th grade B" group, there is a notable strong understanding and skills in the evaluated areas, although the aim is to achieve a higher level of excellence beyond the current "AD" level. On the other hand, the "4th grade C" group displays consistent performance at levels "A" and "B," underscoring the importance of fostering deeper understanding and the application of innovative approaches. In the "4th grade D" group, a consistent pattern of achievements at levels "A" and "B" is observed, indicating a solid foundation in the competencies. The absence of achievements at the "C" level suggests satisfactory performance. In conclusion, the work experience demonstrates promising results in the role of an educator. The pedagogical approach, focused on interdisciplinary and technological integration, contributes to a strong understanding of the evaluated competencies.